INTENSITAS SERANGAN PENYAKIT VASCUAR STREAK VSD PADA BEBERAPA KLON KAKAO DI DESA SIDONDO III - N.Hi.Topae, Irwan Lakani, Johanis Panggeso, Febrianto (AGROTEKBIS, 2016)
This study aims to determine the intensity of the disease Vascular Streak Dieback (VSD) in some cocoa clones in the village of the District III Sidondo Sigi Biromaru. This study was conducted in cocoa plantations in the village of the District III Sidondo Sigi Biromaru 01 ° 06 01.9 "latitude and 199 ° 54 56,0 BT 61 M above sea level. The study took place in the third week of February 2015 until the second week of April 2015. In this study used six types of clones observed that cocoa Local, S2 clone, M01 clone, Phanter clone, ICCRI 1 clone and Irian  clone. This study used survey methods and in the determination of the observation plots using Priposive Sampling method in which each set of 15 plants cocoa clones to be observed. Based on observations VSD disease in cacao plantations in the village of Sidondo III shows that the six types of cocoa clones observed have experienced any symptoms of infection VSD. From the intensity calculation data VSD disease attacks on each clone kakaodi Sidondo village III shows the percentages of different clones S2 is on average 3.53%, 4.02% Irian clones, ICCRI 1 4.43%, 4.575 M01 clones, clones Phanter 4.65% and 15.16% local cocoa. Based on the results of the calculation of the rate of fungus infection O. theobromae on cocoa clones 6 In the village Sidondo III shows the rate of infection is quite low at Cocoa Locale 0, 1307 cm², S2 0, 2195 cm², M01 0, 2207 cm², Phanter 0, 1652 cm², ICCRI 1 0, 1 348 cm² and Irian 0, 2887 cm².